2020
DOI: 10.2196/14570
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized eHealth Intervention for Lifestyle Changes in Patients With Cardiovascular Disease: Randomized Controlled Trial

Abstract: Background Behavior change methods involving new ambulatory technologies may improve lifestyle and cardiovascular disease outcomes. Objective This study aimed to provide proof-of-concept analyses of an intervention aiming to increase (1) behavioral flexibility, (2) lifestyle change, and (3) quality of life. The feasibility and patient acceptance of the intervention were also evaluated. Methods Patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 33 publications
(36 reference statements)
1
50
0
Order By: Relevance
“…The summary of analysis is provided in Table 3, which lists the themes/observations from reviewers that correspond with the objective statement and sorts articles from the most recent to the oldest. [25] Not reported Convenience of telemedicine, increased patientprovider communication, concerns adequately addressed, increased access Strong satisfaction Richards et al [24] Some patients prefer in-person consultations, technical literacy Pandemic created acceptance of technology, past experience with technology Not reported Kurihara et al [23] Technology needs further development, technical literacy Technical literacy, past experience with technology, perceived usefulness, increased patient-provider communication, perceived ease of use Not reported Alkirie et al [26] Technology needs further development Increased connectedness, self-management, flexibility, and access Not reported Ballin et al [27] Health literacy, availability of technology, technical literacy Enabled social interaction; decreased anxiety; increased connectedness, technical literacy, and access; televideo enables reading of body language; education; convenience of telemedicine Not reported Banbury et al [28] Technology needs further development, decrease in patient-provider communication, technical literacy, confidentiality/security Increased efficiency, access, and patient-provider communication, and improved standard of care Not reported Barnett et al [29] Discomfort for wearable monitors, technical literacy, technology needs further development Technical literacy, increased self-management, increased access, increased flexibility Not reported Batalik et al [30] Limits of reimbursement for telemedicine, some patients prefer in-person consultations, connectivity, technical literacy Pandemic created acceptance of technology, availability of technology, fewer miles driven to appointment, convenience of telemedicine, faster initiation of treatment, decreased costs Not reported Beller et al [31] Perceived lack of usefulness, lack of personal desire to get better, some patients prefer inperson consultations Increased connectedness, increased adherence, improved health behaviors Not reported Bernabe-Ortiz et al [32] Not reported Pandemic created acceptance of technology Not reported Bilgrami et al [33] Decrease in quality of life after intervention Perceived usefulness, perceived ease of use, increased adherence Strong satisfaction Broers et al [34] Technical literacy, availability of technology Increased adherence, increased self-management, increased weight loss, technical literacy Not reported Cho et al [35] Technology needs further development Technical literacy, perceived ease of use Not reported Claes et al [36] Lack of personal desire to get better, technology needs further development, technical literacy Increased adherence, increased self-management Not reported Coorey et al [37] Technology needs fur...…”
Section: Thematic Analysis Based On Results Of Individual Studiesmentioning
confidence: 99%
“…The summary of analysis is provided in Table 3, which lists the themes/observations from reviewers that correspond with the objective statement and sorts articles from the most recent to the oldest. [25] Not reported Convenience of telemedicine, increased patientprovider communication, concerns adequately addressed, increased access Strong satisfaction Richards et al [24] Some patients prefer in-person consultations, technical literacy Pandemic created acceptance of technology, past experience with technology Not reported Kurihara et al [23] Technology needs further development, technical literacy Technical literacy, past experience with technology, perceived usefulness, increased patient-provider communication, perceived ease of use Not reported Alkirie et al [26] Technology needs further development Increased connectedness, self-management, flexibility, and access Not reported Ballin et al [27] Health literacy, availability of technology, technical literacy Enabled social interaction; decreased anxiety; increased connectedness, technical literacy, and access; televideo enables reading of body language; education; convenience of telemedicine Not reported Banbury et al [28] Technology needs further development, decrease in patient-provider communication, technical literacy, confidentiality/security Increased efficiency, access, and patient-provider communication, and improved standard of care Not reported Barnett et al [29] Discomfort for wearable monitors, technical literacy, technology needs further development Technical literacy, increased self-management, increased access, increased flexibility Not reported Batalik et al [30] Limits of reimbursement for telemedicine, some patients prefer in-person consultations, connectivity, technical literacy Pandemic created acceptance of technology, availability of technology, fewer miles driven to appointment, convenience of telemedicine, faster initiation of treatment, decreased costs Not reported Beller et al [31] Perceived lack of usefulness, lack of personal desire to get better, some patients prefer inperson consultations Increased connectedness, increased adherence, improved health behaviors Not reported Bernabe-Ortiz et al [32] Not reported Pandemic created acceptance of technology Not reported Bilgrami et al [33] Decrease in quality of life after intervention Perceived usefulness, perceived ease of use, increased adherence Strong satisfaction Broers et al [34] Technical literacy, availability of technology Increased adherence, increased self-management, increased weight loss, technical literacy Not reported Cho et al [35] Technology needs further development Technical literacy, perceived ease of use Not reported Claes et al [36] Lack of personal desire to get better, technology needs further development, technical literacy Increased adherence, increased self-management Not reported Coorey et al [37] Technology needs fur...…”
Section: Thematic Analysis Based On Results Of Individual Studiesmentioning
confidence: 99%
“…For people with NCDs, in addition to obtaining traditional medical treatment, it is essential to adopt a healthy lifestyle through health care intervention in order to avoid further progression and relapse of NCDs [4]. In the recent 15 years, multiple health behavior change (MHBC, namely addressing no less than 2 health behaviors within a limited time period) has demonstrated early success in facilitating a healthy lifestyle among people with NCDs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Do CHANGE 2 program implemented in this trial was similar to that described by Broers et al for Do CHANGE 1 [ 20 ]. Patients randomized to the intervention group received devices for measuring key clinical parameters needed for monitoring their CVD, such as a BP monitor, weight scale (in HF patients only), and the Careportal, which allowed monitoring of daily symptoms and an electrocardiogram.…”
Section: Methodsmentioning
confidence: 99%
“…Patients received a total of 32 do’s during the 3-month intervention period (2-3 do’s per week). The program was tailored to the cardiac population with slight differences in the program depending on patients’ primary diagnosis (coronary artery disease, heart failure, and hypertension), as the preferred health behaviors may vary depending on the diagnosis [ 20 ]. In order to obtain objective measures on patients’ physical functioning, all participants received a BP monitor, the Moves app (Facebook Inc; to register GPS location), and the Careportal (Docobo Ltd, home monitoring device measuring daily symptoms and an electrocardiogram).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation